Hígado graso no alcohólico como factor de riesgo para infarto agudo de miocardio: Non-alcoholic fatty liver disease as a risk factor for acute myocardial infarction - Alfaro-Araujo , Olenka Xiomara (2024)
Objetive: To determine if non-alcoholic fatty liver disease is a risk factor for acute myocardial infarction. Methods: Retrospective case-control study, which included 171 medical records of adult patients, of whom were divided into 2 groups: 57 patients with acute myocardial infarction and 114 without acute myocardial infarction. Statistical tests were the Odds Ratio (OR) and logistic regression. Results: The frequency of NAFLD in patients with acute myocardial infarction was 59.6%, the frequency of NAFLD in patients without acute myocardial infarction was 28.1%. Regarding the multivariate analysis, arterial hypertension (p=0.015; OR=2.729), advanced age (p=0.04; OR=2.281) and male sex (p=0.047; OR=2.157) were risk factors for acute myocardial infarction. myocardium. Conclusion: NAFLD is a risk factor for acute myocardial infarction.